(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objective: This in-vitro study was to investigate enamel surface compositional changes using CO2 (10.600nm) and infrared diode laser (980nm) and their ability to increase its resistance to demineralization. Methods: Seventy premolar teeth, extracted for orthodontic reasons. The samples were randomly divided into three groups. group 1control ten samples group group 2 C02 laser, group 3 diode laser group thirty samples for each was divided into three sub group according to parameter 2,4, 6 watt for one minute after irradiation the samples were immersed in acetate buffer (ph 4.5) and incubated at 37OC for 24 hours and then acid resistance were evaluated by determining calcium ion concentration by energy dispersive x-ray spectroscopy (EDX). Data were collected, tabulated and analyzed. The results showing 2w: There was no statistically significant difference between (Co2) and (Diode) where (p=0.139). The highest mean value was found in (Diode) while the least mean value was found in (Co2).4w: There was no statistically significant difference between (Co2) and (Diode) where (p=0.432). The highest mean value was found in (Diode) while the least mean value was found in (Co2) 6w: There was a statistically significant difference between (Co2) and (Diode) where (p=0.011). The highest mean value was found in (Diode) while the least mean value was found in (Co2). The study concluded: Laser application is a promising technique for tissue remineralization and to increase the enamel resistance against the bacterial acid attack.